2003
DOI: 10.1124/dmd.31.11.1448
|View full text |Cite
|
Sign up to set email alerts
|

PHARMACOKINETICS AND METABOLISM OF [14C]EPLERENONE AFTER ORAL ADMINISTRATION TO HUMANS

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:A pharmacokinetics and metabolism study was conducted in eight healthy human volunteers. After oral administration of EP and its metabolites did not preferentially partition into the red blood cells and blood concentrations of total radioactivity were lower than plasma concentrations. Approximately 66.6% and 32.0% of the radioactive dose were excreted in urine and feces, respectively. The majority of urinary and fecal radioactivity was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 12 publications
1
40
0
3
Order By: Relevance
“…The absolute bioavailability of eplerenone is not known; however, balance studies have shown that it is rapidly absorbed from any of a number of intestinal sites including the duodenum, jejunum, colon, and rectum with a maximum concentration (C max ) of 1.3-hrs [19]. There are no known fooddrug interactions with eplerenone.…”
Section: Eplerenonementioning
confidence: 98%
See 2 more Smart Citations
“…The absolute bioavailability of eplerenone is not known; however, balance studies have shown that it is rapidly absorbed from any of a number of intestinal sites including the duodenum, jejunum, colon, and rectum with a maximum concentration (C max ) of 1.3-hrs [19]. There are no known fooddrug interactions with eplerenone.…”
Section: Eplerenonementioning
confidence: 98%
“…As a percentage of dose, the primary metabolites excreted in urine and feces included 6β-hydroxy-EP (6β-OHEP) (32.0%), 6 β, 21-OHEP (20.5%), 21-OHEP (7.89%), and 2α, 3 β, 21-OHEP (5.96%). The amounts of the other metabolites excreted are less than 5% each [19].…”
Section: Eplerenonementioning
confidence: 98%
See 1 more Smart Citation
“…After a stabilization period of 15 min, the hearts were perfused with the control samples for another 10 min before ischemia-reperfusion in order to measure the baseline pre-ischemia cardiac function. In the aldosterone preconditioning groups, 10 K9 mol/l of aldosterone (Wako Pure Chemical Industries, Osaka, Japan) with or without 10 K6 mol/l of the MR antagonist eplerenone (SigmaAldrich, the dose used in the previous study using a rat Langendorff perfusion model in order to substantially block the MR-dependent action (Chai et al 2006), as well as on the basis of the pharmacokinetics of eplerenone after oral administration to humans (Cook et al 2003)), 10 K7 mol/l of the glucocorticoid receptor (GR)/progesterone receptor antagonist RU486 (Sigma-Aldrich), 10 K7 mol/l of the G protein-coupled estrogen receptor (GPER, previously known as G protein-coupled receptor 30 (GPR30)) antagonist G15 (Cayman Chemical, Ann Arbor, MI, USA), or 10 K5 mol/l of p38MAPK inhibitor SB203580 (Tocris, Bristol, UK) was added to the buffer during the 10-min pre-ischemia perfusion period. Where indicated, 10 K6 mol/l of eplerenone alone was also perfused during the 10-min pre-ischemia period only.…”
Section: Ischemia-reperfusion Modelmentioning
confidence: 99%
“…Der Metabolismus ist überwiegend durch Hydroxylierung geprägt. Dabei entstehen 4 Hauptmetabolite, die als inaktiv gelten und zusammen mit Eplerenon 75% der Dosis ausmachen [71,72,73]. Die Ausscheidung der Metabolite erfolgt weit überwiegend renal (etwa 60%).…”
Section: Pharmakokinetikunclassified